2008
DOI: 10.1159/000137655
|View full text |Cite
|
Sign up to set email alerts
|

[<sup>18</sup>F]-DOPA Positron Emission Tomography for Preoperative Localization in Congenital Hyperinsulinism

Abstract: In recent years, considerable progress has been made in the biochemical, morphological and molecular genetic differentiation of congenital hyperinsulinism (CHI). Fluorine-18 L-3,4-dihydroxyphenylalanine positron emission tomography (18F-DOPA-PET) has been introduced for differentiation between focal and diffuse CHI. The ability to take up L-DOPA and convert it into dopamine is correlated with the activity of the aromatic amino acid decarboxylase and increased in the hyperfunctional affected pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 111 publications
0
45
0
1
Order By: Relevance
“…Indeed, benign insulinomas are routinely localised against the pancreatic background using these agents [10]. In addition, it was shown that F-DOPA uptake could differentiate between the focal and diffuse forms of congenital hyperinsulinaemia, which in itself constitutes direct imaging of beta cell mass and dysfunction [11]. The full serotonergic metabolic pathway has recently been described in the pancreatic beta cell, as has been the expression of several serotonin receptors in beta, alpha and delta cells [12,13].…”
Section: Principles Of Radiotracer Development For Beta Cell Massmentioning
confidence: 99%
“…Indeed, benign insulinomas are routinely localised against the pancreatic background using these agents [10]. In addition, it was shown that F-DOPA uptake could differentiate between the focal and diffuse forms of congenital hyperinsulinaemia, which in itself constitutes direct imaging of beta cell mass and dysfunction [11]. The full serotonergic metabolic pathway has recently been described in the pancreatic beta cell, as has been the expression of several serotonin receptors in beta, alpha and delta cells [12,13].…”
Section: Principles Of Radiotracer Development For Beta Cell Massmentioning
confidence: 99%
“…The focal form is caused by a paternally inherited ABCC8 or KCNJ11 gene mutation, whereas several other mutations are associated with the diffuse form, and in 50% of the cases the genetic basis is unknown (22). The introduction of 18 F-FDOPA PET and later PET/CT have made a tremendous change in the management of infants with the focal disease who can now be cured by molecular imaging-guided laparoscopic surgery (23). The sensitivity and specificity of 18 F-FDOPA PET for detecting a focus usually measuring between 2 and 10 mm is approximately 90% and 100%, respectively (21).…”
Section: Neonatal and Adult Hyperinsulinismmentioning
confidence: 99%
“…Fluorine-18 L-dihidroksifenilalanin pozitron emisyon tomografi (18-F L-DOPA PET) taramasıyla, primer veya metastatik pankreas tümörü yanı sıra hiperfonksiyone pankreas hücreleri tanınabilir. Cerrahi girişim açısından yol gösterici nitelikte olan L-DOPA PET sayesinde lezyonun diffüz veya fokal olup olmama özelliği tanımlanabilir (15) . Olgumuzun yapılan batın MRG'sinde pankreas yapısı normal olarak değerlendirildi.…”
Section: Discussionunclassified